3D printing of potassium sodium niobate by binder jetting: Printing parameters optimisation and correlation to final porosity - Francesco Bertolini; Marco Mariani; Elisa Mercadelli; Carlo Baldisserri; Carmen Galassi; Claudio Capiani; Raffaele Ardito; Nora Lecis (Journal of Materials Research and Technology, 2024)
Binder Jetting (BJT) is a non-fusion-based Additive Manufacturing (AM) technique. It consists of the selective deposition of a liquid binder to join powder particles, thereby enabling the creation of near-net-shaped parts.In this study, the main printing parameters correlated to the binder distribution and infiltration (binder saturation, binder set time, drying time, and target bed temperature) were optimised to improve the precision of green parts printed with potassium sodium niobate (KNN) powder. The optimisation procedure was conducted using the Taguchi statistical method. An L9 orthogonal array with four factors of control at three levels each was employed. The analysis showed that the drying time had the greatest influence on the precision of green parts, followed by binder saturation and target bed temperature. Binder set time did not seem to affect the results.Dimensional analysis, microstructural and piezoelectric characterisation of parts densified by pressureless sintering were conducted. The highest average relative density exceeded 80% for the specimens printed with the lower binder saturation. Piezoelectric properties exhibit more complex behaviour. The prolonged infiltration of larger binder volumes is correlated to higher g33, thus FOMh and FOM33, and lower values for ε33T. On the other hand, d33 does not display a specific dependence on density or printing parameters.The results of this study indicate that BJT can be used to fabricate high-precision KNN components with good piezoelectric properties. The optimisation of printing parameters is essential to achieve the desired results.